2022
DOI: 10.3390/cells11020244
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill Exercise Prevents Decline in Spatial Learning and Memory in 3×Tg-AD Mice through Enhancement of Structural Synaptic Plasticity of the Hippocampus and Prefrontal Cortex

Abstract: Alzheimer’s disease (AD) is characterized by deficits in learning and memory. A pathological feature of AD is the alterations in the number and size of synapses, axon length, dendritic complexity, and dendritic spine numbers in the hippocampus and prefrontal cortex. Treadmill exercise can enhance synaptic plasticity in mouse or rat models of stroke, ischemia, and dementia. The aim of this study was to examine the effects of treadmill exercise on learning and memory, and structural synaptic plasticity in 3×Tg-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 82 publications
1
39
0
Order By: Relevance
“…Nowadays, physical activity and exercise have been widely acknowledged as effective strategies for improving AD pathology and AD-associated cognitive impairment ( Northey et al, 2018 ; Jia et al, 2019 ; de Farias et al, 2021 ). From a mechanistic perspective, macroscopically, regular exercise has been shown to alleviate some abnormalities of brain structure and function and to increase cerebral blood flow in subjects with mild cognitive impairment (MCI) and AD ( Broadhouse et al, 2020 ; Tomoto et al, 2021 ; Yu et al, 2021 ); microscopically, exercise training not only increases levels of exerkines (e.g., irisin, Lourenco et al, 2019 ; Islam et al, 2021 ) and metabolic factors (e.g., lactate, El Hayek et al, 2019 ) in the peripheral circulation, which act on the AD brain indirectly, but also exert direct neuroprotective effects by increasing levels of brain-derived neurotrophic factor (BDNF) ( Wang and Holsinger, 2018 ) and promoting adult hippocampal neurogenesis ( Choi et al, 2018 ), enhancing synaptic plasticity ( Mu et al, 2022 ), reducing neuroinflammation and oxidative stress ( Zhang et al, 2019 ), and ameliorating Aβ deposition and tau hyperphosphorylation ( Brown et al, 2019 ). Strikingly, the activity of central neurotransmitter systems seems to be strongly modulated by exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, physical activity and exercise have been widely acknowledged as effective strategies for improving AD pathology and AD-associated cognitive impairment ( Northey et al, 2018 ; Jia et al, 2019 ; de Farias et al, 2021 ). From a mechanistic perspective, macroscopically, regular exercise has been shown to alleviate some abnormalities of brain structure and function and to increase cerebral blood flow in subjects with mild cognitive impairment (MCI) and AD ( Broadhouse et al, 2020 ; Tomoto et al, 2021 ; Yu et al, 2021 ); microscopically, exercise training not only increases levels of exerkines (e.g., irisin, Lourenco et al, 2019 ; Islam et al, 2021 ) and metabolic factors (e.g., lactate, El Hayek et al, 2019 ) in the peripheral circulation, which act on the AD brain indirectly, but also exert direct neuroprotective effects by increasing levels of brain-derived neurotrophic factor (BDNF) ( Wang and Holsinger, 2018 ) and promoting adult hippocampal neurogenesis ( Choi et al, 2018 ), enhancing synaptic plasticity ( Mu et al, 2022 ), reducing neuroinflammation and oxidative stress ( Zhang et al, 2019 ), and ameliorating Aβ deposition and tau hyperphosphorylation ( Brown et al, 2019 ). Strikingly, the activity of central neurotransmitter systems seems to be strongly modulated by exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous functions regulated by GS14 in the spines include the role of various G proteins and Ca2+/calmodulin signaling [ 76 ]. Another study has demonstrated the increased number and activity of spines, reduced in a mouse family affected by an Alzheimer’s disease model, reaches values of normal mice after months of treadmill exercise [ 77 ]. It appears, therefore, that brain functions, including learning and memory, can be protected at the level of spines by appropriate physical exercise.…”
Section: Post-synapses With Spinesmentioning
confidence: 99%
“…This section is not entirely distinct from the previous ones. Indeed, many studies about structure and function of post-synapses, especially those concerning the spines, include sections dealing with diseases; see for example [ 16 , 25 , 53 , 73 , 75 , 77 ]. The difference between the previously mentioned articles and those of this section deals not with different areas but with different approaches, the most important in the present section.…”
Section: Post-synapse Alterations In Brain Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have shown that physical exercise decreases Aβ burden and alleviates synapse loss and impairment of learning and memory in mouse models [ 28 , 29 , 30 ]. Meanwhile, exercise reduces the activation of microglia and astrocytes and neuroinflammation and preserves cognitive function in 3 × Tg-AD mice [ 31 ].…”
Section: Introductionmentioning
confidence: 99%